Visualisasi Personalitas dan Pesan pada Poster Kampanye terhadap Keputusan Pemilih dalam Pemilu 2024 - Syamsul Arif Billah; Ajeng Ayu Wulandari; Adi Junaedi (JIKE: Jurnal Ilmu Komunikasi Efek, 2024)
voter decisions in the 2024 elections. Analyzing these elements is crucial because they directly influence voter perceptions and decisions. Understanding this impact will help in devising more effective campaign strategies and enhancing overall visual communication. The theoretical framework used includes the First Impression Theory and the Election Decision Theory. The variables analyzed include facial expressions, clothing and appearance, visual context, symbolic iconography, balance of proportions, and visual communication messages. Data was collected through Likert scale questionnaires and analyzed on 100 respondents using Purposive Sampling based on the Taro Yamane formula. The study's results show that the variables of facial expressions, symbolic iconography, balance of proportions, and visual communication messages have a positive and significant impact on voter decisions. Conversely, the variables of clothing and appearance and visual context do not have a significant influence. Determination analysis reveals that visual communication messages contribute 25.6% to voter perception, while decision-making is influenced by 6.4%. This research contributes to the field of political communication by demonstrating how visual elements can affect voter decisions in political campaigns. Keywords: Facial expressions, visual context, symbolic iconography, and visual communication messages.